A colorimetric method for the determination of different functional flavonoids using 2, 2'-azino-bis-(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and peroxidase. Issue 10 (26th November 2019) - Marín, Francisco R.; Hernández-Ruiz, Josefa; Arnao, Marino B.
Abstract: In many occasions it is necessary to use fast and simple methods, different to the chromatographic techniques, for the quantification of biomolecules such as flavonoids. Also, the flavonoid levels in some foodstuffs can be influenced by industrial extraction processes such as pressing and squeezing, resulting in modification of their functional value. For this purpose, we have developed a rapid method to analyze flavonoids, based on a coupling reaction between ABTS and flavonoid mediated by peroxidase. The present method can be used to detect and measure flavonoids with hydroxyl moieties on A- or B-rings, not adjacent to methoxy or oxo substitutions. The visible spectrum of the ABTS-flavonoid complex, the calibration curve (within the range 5-50 μM) and the molar absorption coefficients for isosakuranetin, isonaringin, rhoifolin, hyperoside, rutin, hesperetin, quercetin, kaempherol and naringenin are given. The method has been applied to complex culture media and is sensitive, accurate, quick and easy to apply. This method can be used in laboratories that do not have sophisticated and expensive techniques such as liquid chromatography and also as a quick, simple and inexpensive technique for student practice laboratories.